Mundo Bit Byte - A digital mobile game to disseminate female personalities that made history in Computing - Araujo, Aleteia (2022)
There are great female personalities in the history of computing who have played an important role in the historical achievements of this area. However, their contributions are often poorly publicized and/or credit for those contributions is denied to the true authors. Thus, this paper proposes a game called Mundo Bit Byte, created by a team of female undergraduates and high school girls. The story is based on five prominent female personalities in the field of Computing. Each phase of the game is inspired by the life of one of these women, showing, in a playful and fun way, their achievements and other relevant aspects of their lives. A demo version of the game containing two phases was evaluated by 511 people. In the first test, 234 responses were obtained, and in the second test, 277. Most respondents (97.4% in first test and 98.2% in second one) reported that they would like to meet other important women in computing after playing Mundo Bit Byte. The results indicated that games like this can be powerful tools to reduce stereotypes in the Computing area.